2015
DOI: 10.1097/inf.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Polymorphism of IL-17 G-152A is Associated with Increased Colonization of Streptococcus pneumoniae in Young Finnish Children

Abstract: Our results indicate that IL-17 G-152A is associated with increased colonization rate of S. pneumoniae in young children, suggesting that IL-17A plays an important role in protection against pneumococcal colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…Furthermore, patients with autosomal dominant hyper-IgE syndrome (Job's syndrome), who lack the ability to generate memory Th17 cells due to mutations in the STAT3 gene, are highly susceptible to recurrent pneumococcal infections (9,10). More recently, two studies provided support for a role of IL-17A in pneumococcal carriage in children: a specific polymorphism of the IL-17 gene (G152A) in Finnish children (11) and decreased IL-17A secretion in Fijian children (12) were associated with increased risks of pneumococcal carriage.…”
mentioning
confidence: 99%
“…Furthermore, patients with autosomal dominant hyper-IgE syndrome (Job's syndrome), who lack the ability to generate memory Th17 cells due to mutations in the STAT3 gene, are highly susceptible to recurrent pneumococcal infections (9,10). More recently, two studies provided support for a role of IL-17A in pneumococcal carriage in children: a specific polymorphism of the IL-17 gene (G152A) in Finnish children (11) and decreased IL-17A secretion in Fijian children (12) were associated with increased risks of pneumococcal carriage.…”
mentioning
confidence: 99%
“…Our observations differed from the findings of a Finnish study that measured serum IL-17A in 93 of the 405 controls included in the present study at 13 months of age. That study found that IL-17A was detectable in 6% of the variant AA homozygotes, in 33% of the variant GA heterozygotes and in 75% of the wild GG homozygotes (12). The concentrations were much higher in the adults in the present study: the median was 26.3 pg/mL in those with the variant genotype and 28.94 pg/mL in those with the wild genotype, compared to <1.25 pg/mL and 2.5 pg/mL in the infant controls, respectively (12).…”
Section: Discussionmentioning
confidence: 92%
“…That study found that IL-17A was detectable in 6% of the variant AA homozygotes, in 33% of the variant GA heterozygotes and in 75% of the wild GG homozygotes (12). The concentrations were much higher in the adults in the present study: the median was 26.3 pg/mL in those with the variant genotype and 28.94 pg/mL in those with the wild genotype, compared to <1.25 pg/mL and 2.5 pg/mL in the infant controls, respectively (12). The measurements were carried out with the same method in the same laboratory, which means that the differences were not technical.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly to the other cytokines mentioned above, gene polymorphism has been observed in IL-17, IL-23, and the IL-23 receptor. Previously, IL-17 polymorphism has been associated with increased bacterial colonization and childhood asthma (Chen et al 2010;Vuononvirta et al 2015).…”
Section: Introductionmentioning
confidence: 99%